Anti-Inflammatory and Antioxidant Activities of Pycnanthus angolensis and Daniellia oliveri in Relation to Their Traditional Use in the Treatment of Dysmenorrhea - Kouassi Konan Armand Marcelin; Kambou Sansan Philippe; Assoumou Akoua Tina Isabelle; Trébissou Johnson Noël David; N’guessan Jean David (Advances in Pharmacological and Pharmaceutical Sciences)
Dysmenorrhea is a painful condition that precedes or accompanies menstruation. It is a real problem for women of reproductive age and impacts their quality of life. The present study aims to assess the anti-inflammatory and antioxidant properties of Pycnanthus angolensis and Daniellia oliveri, two plants traditionally used to treat dysmenorrhea. The anti-inflammatory activity of aqueous extracts of stem barks of P. angolensis and root barks of D. oliveri was carried out on Wistar rats using the carrageenan-induced paw edema method. The antioxidant activity was assessed in vitro using the 1,1-Diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay. The results showed that aqueous extracts of both plants (at doses of 100 and 200 mg/kg) significantly reduced rat paw edema at 1, 2, 3, 4, 5 and 6-h postcarrageenan injection. The maximum edema-inhibiting activity was reached at the second hour with inhibition of 63.18% for the P. angolensis extract at 200 mg/kg and 58.82% for the D. oliveri extract at 200 mg/kg bw. For the antioxidant activity, the aqueous stem bark extract of P. angolensis, with an antiradical power (AP) of 2.15 μmol DPPH scavenged/mg extract, exhibited better anti-free radical activity compared with that of the aqueous root bark extract of D. oliveri (AP = 0.16 μmol DPPH scavenged/mg extract). These results show that aqueous extracts of P. angolensis and D. oliveri have anti-inflammatory and antioxidant properties.